The Tazkiyatun Nafs (Purification of the Soul) for Enhancing Muslim Family Resilience in the Digital Era - Sugeng Sejati; Naylatun Ni'mah; Widya Putri; Fifian Revalina (DAWUH : Islamic Communication Journal, 2026)
This study examines the role of tazkiyatun nafs (spiritual purification of the soul) in enhancing Muslim family resilience in the digital era. Rapid technological advancement, excessive social media use, and digital dependency have created challenges for family communication, emotional stability, and moral cohesion. This research employed a Systematic Literature Review (SLR) following PRISMA guidelines and analyzed 25 peer-reviewed articles published between 2015 and 2025 from Scopus, ScienceDirect, DOAJ, and Google Scholar. The findings indicate that tazkiyatun nafs, through the stages of takhalli, tahalli, and tajalli, strengthens family resilience at three interconnected levels: intrapersonal, interpersonal, and transpersonal. The process promotes emotional regulation, self-control, empathetic communication, constructive conflict resolution, and shared spiritual meaning within family relationships. The study further demonstrates that spiritual purification complements psychological resilience mechanisms by providing an internal moral and spiritual foundation that helps families cope with technoference, social comparison, and digital overexposure. These findings highlight the relevance of integrating Islamic spiritual principles with contemporary psychological approaches to foster resilient Muslim families in the digital era. The study offers practical implications for Islamic family counseling, digital literacy programs, and spirituality-based family resilience interventions.